2017
DOI: 10.3126/ijasbt.v5i4.18620
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Combined Antibiotic and Methanol Extract of Eucalyptus camaldulensis leaf Against Staphylococcus aureus and Pseudomonas aeruginosa

Abstract: A total of seventy-five medical specimens were collected from different patients admitted to Zagazig university hospital, Egypt. The selected bacterial isolates were distributed as 45 Gram negative bacterial isolates and 30 Gram positive bacterial isolates. The most effective antibiotic was gentamycin followed by amikacin and nitrofurantoin. The multi-drug resistant (MDR) bacterial isolates were selected and identified to four groups; Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia coli and Staphylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
1
7
0
2
Order By: Relevance
“…Similarily, the increase of β-lactamase produing MRSA and E. coli sensitivity to cephalexin, cefuroxime, amoxicillin, and ampicillin has been obtained through combination with E. camaldulensis EOs (Chaves et al, 2018). Synergistic activity has been recorded between E. camaldulensis plant extracts and gentamicin or ceftriaxone against MDR S. aureus and P. aeruginosa (Reda et al, 2017;Ibrahim et al, 2014), as well as in combination with ampicillin against S. aureus (Ibrahim et al, 2014).…”
Section: Interaction Of Eucalyptus Camaldulensis Dehn Eos/extracts Amentioning
confidence: 83%
See 1 more Smart Citation
“…Similarily, the increase of β-lactamase produing MRSA and E. coli sensitivity to cephalexin, cefuroxime, amoxicillin, and ampicillin has been obtained through combination with E. camaldulensis EOs (Chaves et al, 2018). Synergistic activity has been recorded between E. camaldulensis plant extracts and gentamicin or ceftriaxone against MDR S. aureus and P. aeruginosa (Reda et al, 2017;Ibrahim et al, 2014), as well as in combination with ampicillin against S. aureus (Ibrahim et al, 2014).…”
Section: Interaction Of Eucalyptus Camaldulensis Dehn Eos/extracts Amentioning
confidence: 83%
“…Minimal inhibitory concentrations in most studies were in range 0.07-0.5% indicating moderately high activity against this bacterium. Beside S. aureus, antibacterial effect was confirmed against B. subtilis (0.17-0.34%), M. luteus (0.2-0.4%), and S. pyogenes (0.4-1.1%) Akin et al, 2010;Knezevic et al, 2016;Khubeiz et al, 2016;Reda et al, 2017;Ostad Asiaei et al, 2018). Activity of EOs was examined aginst L. monocytogenes in only one study and MIC was not obtained with the highest used concentration of 1.0%, and the same was reported for Enterococcus durans (Akin et al, 2010).…”
Section: Antibacterial Effectmentioning
confidence: 98%
“…Also, El-Zawahry et al (2013) reported that the most effective antibiotic for clinical bacterial isolates was amikacin (80%) followed by nitrofurantoin and norfloxacin with susceptibility percentage, 76.25% and 71.25%, respectively. Reda et al (2017) reported that gentamycin (76%) was the most effective antibiotic against clinical bacterial isolates followed by amikacin and nitrofurantoin. Nunes et al (2015) reported that the CNS strains isolated from commercial and artisanal salami showed multi-resistance to several antimicrobials of therapeutic importance in both human and veterinarian medicine, such as β-lactams, vancomycin, and linezolid.…”
Section: Resultsmentioning
confidence: 99%
“…В работе F.M. Reda выявлен синергидный антибактериальный эффект метанолового экстракта из листьев E. camaldulensis в сочетании с гентамицином или цефтриаксоном в отношении штаммов S. aureus и P. aeruginosa, антибактериальная активность в отношении A. baumannii авторами не исследовалась [14]. Заслуживает внимания выраженная бактерицидная активность дербенника иволистного (Lythrum salicaria) в отношении A. baumannii и P. aeruginosa, выявленная в работе E. Guclu [8].…”
Section: материалы и методы исследованияunclassified
“…Одним из перспективных направлений является изучение фармакодинамических взаимодействий вторичных метаболитов расте-ний с антибактериальной активностью и АМП. Описан ряд сочетаний растительных экстрактов и АМП, оказывающих синергидный (взаимно усиливающий) эффект при совместном воздействии на бактериальную клетку [5,14].…”
unclassified